PELATIHAN PENGOLAHAN DAUN KELOR SEBAGAI STRATEGI PENCEGAHAN STUNTING DI DESA SUKAMUKTI - Oktafiani, Andriyana Dwi; Sundari, Kori; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2024)
One of the village governments indirectly involved in preventing and addressing stunting in the Sukamukti Village area is the Sukamukti Village Government in the Bojongmangu District. However, there have been few interventions regarding health issues, especially children's nutrition adequacy in Sukamukti Village. Consequently, stunting has become a major health problem related to children's nutritional needs. The only effort made by the Sukamukti Village Government to prevent stunting is by conducting routine integrated health post activities for pregnant women and toddlers every month. The aim of community service activities in Sukamukti Village is to enhance nutritional knowledge, teach skills in processing locally-sourced complementary feeding like moringa leaf juice, and improve the community's economy through SMEs. The moringa leaf processing training has realized various activities according to plan. First, observation activities were conducted to identify the right targets and obtain permission from local agencies. Second, program planning was carried out to gather several groups and create emotional closeness to ensure smooth implementation. Third, socialization activities were conducted by providing training materials on moringa leaf processing as a stunting prevention strategy in Sukamukti Village. This community service enhances skills, improves nutrition in consumption, and offers broader marketing potential if moringa leaf juice products are turned into SMEs. Additionally, the training provides additional economic benefits by utilizing moringa leaves for various food and beverage variations.